2021
DOI: 10.31234/osf.io/k8me6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mixed-method investigation into measurement reactivity to the experience sampling method: The role of sampling protocol and individual characteristics

Abstract: Since the introduction of the experience sampling method (ESM), there have been concerns that the repeated assessments typically related to this method may alter the behavior, thoughts, or feelings of participants. Previous studies have offered mixed results with some studies reporting reactive changes while others failed to find such effects. Our aim was to investigate under which circumstances ESM induces reactive effects.Students (N = 151) were randomly assigned to receive a questionnaire containing 30 or 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Similarly, among the negative valence emotions, during microdosing days the proportion represented by "ashamed, humiliated, or disgraced" was significantly higher. That "awe, wonder, or amazement" was found to take a more prominent place during microdosing days among positive emotions is in line with results from a recent experimental study (van Elk et al, 2021). However, the results regarding the decrease prevalence of "joyful, glad, or happy" among the positive emotions and the increased prevalence of "ashamed, humiliated, or disgraced" among negative emotions, are surprising.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similarly, among the negative valence emotions, during microdosing days the proportion represented by "ashamed, humiliated, or disgraced" was significantly higher. That "awe, wonder, or amazement" was found to take a more prominent place during microdosing days among positive emotions is in line with results from a recent experimental study (van Elk et al, 2021). However, the results regarding the decrease prevalence of "joyful, glad, or happy" among the positive emotions and the increased prevalence of "ashamed, humiliated, or disgraced" among negative emotions, are surprising.…”
Section: Discussionsupporting
confidence: 83%
“…However, a cautionary note regards our outcome of interest, i.e., a rich emotional life, whose measurement may be the biggest obstacle in compliance. Furthermore, previous research has shown that ESM studies have a habituation period (Eisele et al, 2022), i.e., participants could respond differently throughout the study period of investigation because of getting used to the items presented and also because of the intensive nature of data collection. In our sampling strategy we allowed for breaks in between the observations days and in our analyses we introduced dummies for the observation days, actions meant to address such concerns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 10 discrete emotions that participants had to rate at each measurement occasion were happy, excited, enthusiastic, pleased, relaxed, sad, down, irritated, anxious, and stressed (the specific order was randomized across momentary assessments). The selection of these emotion items was based on their natural occurrence in daily life (ensuring sufficient within-person variability; Eisele et al, 2021) and their balanced combination of different valence and arousal levels (the two most prominent dimensions that underlie our emotional experience according to the circumplex model of affect; Russell, 1980). In our analyses, we considered global momentary positive (PA) and negative affect (NA) composite scores by averaging all same-valenced emotion items at each measurement occasion.…”
Section: Experience Sampling Protocolmentioning
confidence: 99%